Respuesta :

hbj

Answer:

y = -5, 1

Step-by-step explanation:

2y² - 10y + 44 = (y - 7)²

expand (y - 7)²

(y - 7)² = y² - 14y + 49

move it to the left

(2y² - 10y + 44) - (y² - 14y + 49) = 0

distribute the (-)

2y² - 10 y + 44 - y² + 14y - 49 = 0

combine like terms

y² - 4y -5

factor with factoring X

y² + 5y - y - 5 = 0

factor by grouping ↓

factor out a y from first half of equation

y(y + 5) - y - 5 = 0

factor out a (-) from second half of equation

y(y +5) - (y + 5) = 0

(y +5)(y - 1) = 0

y = -5, 1

Otras preguntas

ACCESS MORE